Mali : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The new generation Poverty Reduction Strategy Paper (PRSP) describes the policies and programs that the country intends to implement at the macroeconomic, structural, and social levels. In this study, the new generation PRSP was prepared. The low level of poverty reduction is owed to poor control of population growth and inadequate growth rate of the Malian economy. The three strategic orientations are detailed in thirteen priority areas. The results of the work done by the central and deconcentrated administration are discussed. Two major objectives of the PRSP II are outlined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet